HTLV infection in persons with sexually transmitted diseases in Spain - Ayerdi, Oskar; Benito, Rafael; Ortega, Diego; Aguilera, Antonio; Montiel, Natalia; Pintos, Ilduara; Díaz de Santiago, Alberto; Baza, Begoña; Soriano, Vicente; de Mendoza, Carmen (Frontiers in Immunology, 2023)
Background HTLV-1 infection is a neglected disease, despite estimates of 10 million people infected worldwide and producing life-threatening illnesses in 10% of carriers. Sexual transmission is the main route of contagion. However, HTLV-1 is not listed among sexually transmitted infections (STIs). Methods Serum from all consecutive individuals who had attended six STI clinics across Spain during the last 12 months were tested for HTLV antibodies using a commercial enzyme immunoassay (EIA). Reactive samples were confirmed by immunoblot. Results A total of 2,524 samples were examined. The majority (1,936; 76.7%) belonged to men, of whom 676 (34.9%) were men who have sex with men (MSM) receiving HIV pre-exposure prophylaxis. Although native Spaniards predominated (1,470; 58.2%), up to 593 (23.5%) came from Latin America and 139 (5.5%) were African. A total of 26 individuals were initially EIA reactive and immunoblot confirmed 5 as HTLV-1 and 7 as HTLV-2. All but one HTLV-1+ case came from Latin America. Three were men and two were women. Among Latin Americans, the HTLV-1 seroprevalence was 0.67%. In contrast, all seven HTLV-2+ were native Spaniards and former injection drug users, and all but one were HIV+. Conclusion The rate of HTLV infection among individuals with STIs in Spain is 0.5%, which is greater than in the general population. These results support the introduction of universal HTLV screening in persons who attend clinics for STIs.